Epistemological Foundations In Philosophy Of Science - Sulaiman, Edi Saputra; Rijal, Syamsul (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
The research objectives are to explore epistemological foundations in the philosophy of science and the steps of the scientific method in epistemology. The research method employed in this study is a literature review (library research). The results of the research indicate that: First, the epistemological foundations in the philosophy of science include empiricism-positivism, rationalism, constructivism, and criticism. Second, the steps of the scientific method in epistemology are referred to as logico hypotetico verificative-deducto hypothetico verificative. This involves a logical framework, formulation of hypotheses, and factual verification, which serve as the basis for scientific truth with openness to new truths.